Integration of Pancasila Values in Learning to Build Students' Character in the Digital Era - Yorman (ARMADA : Jurnal Penelitian Multidisiplin, 2026)
This research aims to analyze the integration of Pancasila values in learning and its impact on the formation of student character in the digital era in SMAN and MAN in West Lombok Regency. The research background is based on the increasing challenges of globalization and technological developments that have implications for the moral degradation of students, such as low tolerance, increased bullying, and weak social responsibility. This study uses a qualitative approach with a case study design through observation, interview, and documentation techniques, and is analyzed using the Miles and Huberman interactive model. The results of the study show that the integration of Pancasila values is carried out through contextual learning, project-based learning, and reflective discussions. This strategy is able to increase student engagement and provide a more meaningful learning experience. The impact can be seen in increasing tolerance, social responsibility, national and state awareness, and students' ability to think critically about social issues. This shows that Pancasila education plays a role in forming character holistically, not only cognitive, but also affective and behavioral aspects. However, implementation still faces obstacles in the form of limited teacher competence, the negative influence of social media, and a lack of environmental support. Therefore, it is necessary to strengthen teacher capacity, digital literacy, and collaboration between schools, families, and the community.